“History Lives in the Body”: The Body/Land/History Triad in Linda Hogan’s The Woman Who Watches Over the World - Joanna ZIARKOWSKA (E-REA)
The article attempts to demonstrate how the metaphor of the clay woman’s broken body that opens Linda Hogan’s The Woman Who Watches Over the World establishes the author’s preoccupation with inventing a language invested with the corporeal, appropriate for vocalizing the distinct character of Native American experience and how this metaphor is further developed into a concept of history. In Hogan’s text Native history is inextricably connected with ancestral geography, replicated, like DNA, in contemporary Native bodies. Hogan offers an understanding of history expressed in terms of geographical locations as well as bodily experiences and sensations that are remembered, passed on and inherited in the same way genetic material is transmitted from one agent to another. Hence, history, memory and indigenous bodies become integral and integrated components of contemporary Native American identity.